2006
DOI: 10.1002/dc.20420
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic diagnosis of brain metastasis from hepatocellular carcinoma by squash preparation

Abstract: Hepatocellular carcinoma (HCC) metastasizes to the brain is rare instances. In published series and case reports of metastatic HCC, diagnosis of central nervous system metastases has been determined by histologic methods. We present a case of metastatic HCC of brain diagnosed by squash cytologic preparation. A 69-year-old male, HCV positive, suffering from post-hepatitic cirrhosis, initially diagnosed at age 68 with HCC presented with headaches of increasing frequency and severity. A computed tomography scan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, the cytological findings of brain lesions have not been described in LBC samples because preoperative cytological diagnosis is not commonly practiced. Consequently, brain cytology usually entails just tumor imprints of metastatic lesions and/or squash cytology samples collected intraoperatively . However, the diagnostic contribution of these cytological preparations is limited by artifacts (eg, cell rupture) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cytological findings of brain lesions have not been described in LBC samples because preoperative cytological diagnosis is not commonly practiced. Consequently, brain cytology usually entails just tumor imprints of metastatic lesions and/or squash cytology samples collected intraoperatively . However, the diagnostic contribution of these cytological preparations is limited by artifacts (eg, cell rupture) .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, brain cytology usually entails just tumor imprints of metastatic lesions and/or squash cytology samples collected intraoperatively. 4,[10][11][12][13] However, the diagnostic contribution of these cytological preparations is limited by artifacts (eg, cell rupture). 14 In addition, hard tissues (eg, those with calcifications) are generally not suitable for frozen section preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal vascular proliferation is an important feature in the histological and cytological diagnosis of tumours, including brain tumours. However, cytological analysis of the vasculature of primary gliomas or metastatic brain tumours is rarely reported . This study showed that microvascular proliferations were frequent in metastatic tumours, whereas none were identified in normal/reactive brain tissues and the majority of grade II DA/ODGs.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, a few groups showed a peripheral endothelial rim. This pattern, which is characteristic of HCC and has been described in squash preparations of metastatic HCC, 19 is useful in recognizing hepatic differentiation. Such a trabecular pattern reflects the hepatocellular nature of the neoplasm and must be considered a diagnostic clue because it is rare in other ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%